2003
DOI: 10.1159/000077819
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Long-Term, High-Dose Volume Therapy with 6% Hydroxyethyl Starch 130/0.4 or Crystalloid Solution on Hemodynamics, Rheology and Hemostasis in Patients with Acute Ischemic Stroke

Abstract: Background: This study was performed to investigate the clinical effects of a 4-day volume therapy with a newly developed, 6% hydroxyethyl starch (HES) 130/0.4 versus crystalloid solution, with particular regard to systemic and cerebral hemodynamics, rheology and safety. Methods: In a randomized, double-blind study, 40 patients suffering from an acute ischemic stroke received either 6% HES 130/0.4 or crystalloid solution as continuous infusion over 4 days with a total dose of 6.5 liters. Efficacy parameters st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 17 publications
2
29
0
1
Order By: Relevance
“…[14][15][16][17][18][24][25][26][27][28][29] We shared the commonly held perception that both volume effect and molecule characteristics are among the most important factors in organ protection; however, the current study demonstrated that the HES molecule plays a role in hepatoprotection against reperfusion injury. The infused volume of HES solution (13 mLÁkg -1 ) adjusted to the weight of the rats was within the doses reported for volume repletion in clinical studies.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…[14][15][16][17][18][24][25][26][27][28][29] We shared the commonly held perception that both volume effect and molecule characteristics are among the most important factors in organ protection; however, the current study demonstrated that the HES molecule plays a role in hepatoprotection against reperfusion injury. The infused volume of HES solution (13 mLÁkg -1 ) adjusted to the weight of the rats was within the doses reported for volume repletion in clinical studies.…”
Section: Discussionsupporting
confidence: 71%
“…There is evidence of a better safety profile with HES 130/04 compared with the older colloids, and it is often preferred over pure crystalloid regimens because of its prolonged intravascular half-life and positive impact on blood rheology and tissue oxygenation. [24][25][26][27][28][29] Moreover, Lang et al 18 showed a significant attenuation of inflammatory markers, such as interleukins 6 and 8 and soluble Fig. 1 Alanine aminotransferase (ALT) levels in animals that were subjected to one hour of 70% warm ischemia and two hours of reperfusion and in sham-operated controls.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical studies that have addressed this issue did not show significant changes in plasma viscosity, but neither study was designed to address acute changes following large volume resuscitation. 8,29 Assuming a Newtonian relationship between shear stress and shear rate, pipe flow viscosities for the glycerol/water mixtures and deionized water were found to be in close agreement with those found through capillary viscometry (\ 3%). Any discrepancies between the two measurements can likely be attributed to possible dilution of the HES solutions during pipe flow analysis (system was flushed with water between runs), small deviations during the manual calibration procedure, and the large pressure differences between the nominal pressure involved in capillary viscometry and the high pressures associated with pipe flow.…”
Section: Discussionsupporting
confidence: 67%
“…2,4 Although the merits of effective volume replacement have been well established, there continues to be on-going debate regarding the ideal fluid for volume therapy. 1,2,[5][6][7][8] We focus here on two hydroxyethyl starch (HES) solutions available for volume expansion in Canada, 6% HES 130/0.4 (Voluven Ò , Fresenius Kabi, Bad Homburg, Germany) and 10% HES 260/0.45 (Pentaspan Ò , BristolMyers Squibb Canada, Montreal, QC, Canada). Although pharmacokinetic and risk/benefit profiles have been documented, 9,10 this study examines simple mechanical properties, such as viscosity, that are of critical importance to endothelial cell function and the microvasculature.…”
mentioning
confidence: 99%
“…12 These results have given rise to several phase II preclinical studies investigating the safety of newer generation HES in patients with ischemic stroke. 13,14 Subsequent animal studies have also shown a degree of cerebral protection manifested as decreased infarct volumes in response to focal ischemic injury. Then again, any potential direct clinical relevance was minimized inasmuch as this model employed pretreatment with HES 130/0.4 to a hematocrit of 25-30% prior to development of 120 min of focal ischemia.…”
mentioning
confidence: 99%